Simple Model of Pellet Combustion in Retort Burner - Jozef Micieta; Jiri Hajek; Jozef Jandacka (Communications - Scientific letters of the University of Zilina, 2015)
Combustion of the solid fuel in the burner is an important issue when discussing the CFD simulation of combustion in automatic boiler. In the present work is employed a simplified method for modeling the fuel bed, which is based on mass and heat balances in order to simplify the simulation of combustion in pellet boiler. The model for solid fuel combustion in a burner is created for the purpose of automatic boiler simulations. Such approach does not require a detailed bed model of fired solid fuel. A simple model of the bed can be very useful for designers and engineers of automatic boilers. The described approach to modeling the combustion process in a burner helps to shorten the calculation time and simplify the model of pellet combustion in various types of automatic boilers for households.